Cationic Polyelectrolytes as Drug Delivery Vectors: Calorimetric and Fluorescence Study of Rutin Partitioning - Guangyue Y Bai (2010)
The interaction between hydrophobically modified cationic polysaccharides based on dextran and a flavonoid drug (Rutin) was studied by isothermal titration calorimetry (ITC) and fluorescence spectroscopy, in order to assess the factors responsible for the interaction and characterize its energetics, as well as for evaluating their encapsulation capacity, for possible applicability of these polymers as drug delivery vectors. To address the importance of the hydrophobic pendant groups in the solution behavior of these polymer/drug systems, we also studied the interaction of Rutin with a cationic surfactant, cetyltrimethylammonium chloride (CTAC). The interaction enthalpies and drug binding constants for D40R30/Rutin systems were derived from ITC through a simple binding model. The binding constants were independently derived from fluorescence results, with fair agreement between the parameters obtained from both methods. By changing the Rutin concentration, we were able to get evidence for a solubility enhancement induced by the presence of the polymers, a promising effect regarding its use to improve bioavailability.